Pengaruh Penyuluhan tentang Ciri Seks Sekunder terhadap Pengetahuan Remaja Putri Kelas V di SDN Campurejo Kota Kediri - Machsun Machsun (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
The secondary sex characteristics are physical characteristics that differentiate males and females evolve according to patterns that can be predicted, but at the end of puberty these patterns are already mature or approaching maturity level. With the development of this period, the appearance of boys - men and women are increasingly different. With the change in the majority of teenagers are not able to accept his physical state. Objective: The aim of this study was to determine the effectiveness of education to the knowledge of teenagers (female). The research was pre experiment with the approach of one group pre - post test desaigh. The population was the entire young women and the sample was V grade students, 26 respondents taken with total sampling technique. The data education knowledge of secondary sex characteristics was collected by questionnaire, which were categorized in ordinal scale and analyzed by Wilcoxon. The results of this study was 16 respondents (61.5%) were in good criteria, 8 respondents was in sufficient criteria (30.8%), and 2 respondents were in less criteria (7.7%). The data analysis obtained in the manual calculation results showed the arithmetic value of z = -4.346 <z table = 1,96 proved that H0 and H1 accepted. This means that there was an effect of education on the secondary sex characteristics to the knowledge of young women. The respondents were expected to gain knowledge not only from books but also the health of other media such as electronic media and print media, in addition to the provision of education and education to increase knowledge about the teenage daughter of secondary sex characteristics.